Strategic alliance motivation for technology commercialization and product development. Issue 6 (13th May 2014) - Sompong, Kusumaphorn; Igel, Barbara; Lawton Smith, Helen
Abstract : Purpose: – This paper aims to investigate the relationship among alliance motivation (AM), execution of cooperation (EC) and alliance performance of strategic alliance for commercializing technology and developing products. Design/methodology/approach: – The measurements were constructed and tested empirically through a survey of 320 strategic alliances in the food processing industry in Thailand. Confirmatory factor analysis and structural equation modelling were applied to refine scales for measuring AM, execution and cooperation performance. Findings: – This research found that firms adopted social interaction with alliance partners in order to establish mutual expectations about technology characteristics, access opportunity and organisational management styles, factors that are shown to have positive influences on both commercial and partnership performance. Findings also confirm a significant positive impact of technology characteristics, access opportunity, market potential and financial benefit on the adoption of a formal partnership agreement, but a significant impact only on commercial performance. Research limitations/implications: – Further research should use random samples in different industries in other emerging economies, and other data analysis methods to assess decision-making in strategic technology alliances that may include different types of partnerships. Practical implications: – The findings are also useful for managers who leverage operations with external resources obtained through strategic alliances parameters both in the process of managing relationships and achieving results. Originality/value: – This article contributes to extant literature by developing a practical measurement system of AM, actual EC and resulting performance in an emerging economy country. It also contributes to clarify the decision-making of firms that form strategic alliances for commercializing technology and developing products to facilitate more quality management research in other industries and countries.